2013
DOI: 10.1515/cclm-2012-0488
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of CA 15-3, CEA and serum HER2 in the early detection of recurrence of breast cancer

Abstract: The combination of several tumour markers enhances the sensitivity for detection of metastatic breast cancer. We recommend HER2 or the combination of CEA and HER2 in tissue HER2+ and CA 15-3 or the combination of CA 15-3 and CEA in tissue HER2-.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 23 publications
2
35
0
3
Order By: Relevance
“…Recent studies demonstrated that serial determination of CA 15-3 and CEA levels during the postoperative follow-up of breast cancer patients may be useful for early detection of preclinical recurrence or metastatic disease (8,9). In addition, the serum levels of CA 15-3 and CEA may be used to predict response to chemotherapy in patients with metastatic breast cancer (MBC) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that serial determination of CA 15-3 and CEA levels during the postoperative follow-up of breast cancer patients may be useful for early detection of preclinical recurrence or metastatic disease (8,9). In addition, the serum levels of CA 15-3 and CEA may be used to predict response to chemotherapy in patients with metastatic breast cancer (MBC) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our data indicate that determining the serum concentrations of CEA and CA15-3 provides a simple yet robust method to predict a patient's therapeutic response. However, since our results are based on a retrospective analysis, other tumor markers such as HER-2, epidermal growth factor receptor or tissue polypeptide antigen (25,(39)(40)(41) were not included in our analysis. Analyzing these markers in addition to CEA and CA15-3 could potentially provide even more accurate predictions of therapeutic response than those reported in the present study.…”
mentioning
confidence: 99%
“…HER-2 is not only an important therapeutic target in breast cancer, but as reported by Pedersen et al [ 7 ] high circulating concentrations of this protein may indicate the presence of distant metastases. Moreover, circulating HER-2 may also be used to assess the response to treatment.…”
mentioning
confidence: 83%
“…Distant metastases are in most cases incurable, and early diagnosis of metastatic disease may numerically improve the prognosis only as a result of the leadtime bias. From a practical point of view the only curable recurrence is the local recurrence, but as also shown in the report by Pedersen et al [ 7 ] increased concentrations of tumor biomarkers are rare in patients with isolated local recurrence. Thus, many clinicians see serial determination of tumor biomarkers as being of little help in the practical management of the patient with breast cancer.…”
mentioning
confidence: 87%
See 1 more Smart Citation